Morphology of the Amazonian Teleost Genus Arapaima Using Advanced 3D Imaging - Scadeng, Miriam; McKenzie, Christina; He, Weston; Bartsch, Hauke; Dubowitz, David J.; Stec, Dominik; St. Leger, Judy (Frontiers in Physiology, 2020)
The arapaima is the largest of the extant air-breathing freshwater fishes. Their respiratory gas bladder is arguably the most striking of all the adaptations to living in the hypoxic waters of the Amazon basin, in which dissolved oxygen can reach 0 ppm (mg/l) at night. As obligatory air-breathers, arapaima have undergone extensive anatomical and physiological adaptations in almost every organ system. These changes were evaluated using gross necropsy, histology, magnetic resonance, and computed tomography imaging to create a comprehensive morphological assessment of this unique fish. Segmentation of advanced imaging data allowed for creation of anatomically accurate and quantitative 3D models of organs and their spatial relationships. The deflated gas bladder (1.96% body volume (BV) runs the length of the coelomic cavity, and encompasses the kidneys (0.35% BV). It is compartmentalized by a highly vascularized webbing of trabeculae lined with epithelium acting as a gas exchange surface analogous to a lung. Gills have reduced surface area, with severe blunting and broadening of the lamellae. The kidneys are not divided into separate regions, and have hematopoietic and excretory tissue interspersed throughout. The heart (0.21% BV) is encased in a thick layer of lipid rich tissue. Arapaima have an unusually large telencephalon (28.31% brain volume) for teleosts. The characteristics that allow arapaima to perfectly exploit their native environment also make them easy targets for overfishing. In addition, their habitat is at high risk from climate change and anthropogenic activities. Considering the challenges that face arapaima it is critical that we collect as much information about their unique adaptations before the opportunity is lost.